The Impact of ICT Usage on Energy Consumption Efficiency and Environmental Sustainability in Developing Countries: An Empirical Analysis - Mirza, Faisal Mehmood; Mushtaq, Iqra; Qurat-ul-Ann, Abre-Rehmat; Waheed, Tehreem (Pakistan Journal of Humanities and Social Sciences, 2024)
This study examines the impact of Information and Communication Technologies on energy consumption, energy efficiency, CO2 emissions, and renewable energy adoption in developing countries using the time span of 2007 to 2019 has been used. The results of Generalized Method of Moments reveal that ICT has a multifaceted impact on energy dynamics in developing countries. With increase in ICT adoption, energy consumption increase in developing countrues. Moreover, increase in usage increases CO2 emissions. We find that increase in oil prices encourages the adoption of energy-efficient technologies and reduce CO2 emissions. In constrats, we find limited effect of ICT on renewable energy mainly due to infrastructural barriers in developing countries.